2005
DOI: 10.3126/mjsbh.v7i0.21092
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Aplastic Anemia

Abstract: An Approach to Aplastic Anemia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The most common aetiology of pancytopenia in the present study was aplastic anaemia which is similar with that reported by Kumar et al, Jha et al, Tariq et al, Santra and das, Qamar and Aijaz, Bajracharya et al In their study of 166, 148, 50, 111, 150 and 10 cases respectively. 4,[7][8][9][10][11] The second most common cause was megaloblastic anaemia which is similar with the studies listed above.…”
Section: Causes Of Pancytopeniasupporting
confidence: 58%
“…The most common aetiology of pancytopenia in the present study was aplastic anaemia which is similar with that reported by Kumar et al, Jha et al, Tariq et al, Santra and das, Qamar and Aijaz, Bajracharya et al In their study of 166, 148, 50, 111, 150 and 10 cases respectively. 4,[7][8][9][10][11] The second most common cause was megaloblastic anaemia which is similar with the studies listed above.…”
Section: Causes Of Pancytopeniasupporting
confidence: 58%
“…8 However, there is limited data regarding this from Nepal. 5 The fi rst two common causes of pancytopenia in different studies are compared in Table 6. 3-6, 8-11 In a study by Savage et al and Khunger et al the most common causes of pancytopenia were megaloblastic anemia, followed by hypoplastic anemia and acute leukemia was the third most common in the former study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Few similar studies have been published in the country. 5 This study was carried out with an aim to obtain further information so that it would help in the management of patient with pancytopenia.…”
Section: Introductionmentioning
confidence: 99%
“…The various etiologies of pancytopenia by bone marrow aspiration in the present study were varied, the commonest being Megaloblastic Anemia 67.4% (29 cases), followed by mixed Hypoplastic anemia 23.4% (10 cases), infections (malaria)2.3% (1case), aleukemic leukemia 2.3% (1case), Myelofibrosis 2.3% (1 case), Myelodysplastic syndrome 2.3%(1 case) The results are shown in The first and the second commonest cause of pancytopenia in the present study conducted is Megaloblastic Anemia and Hypoplastic Anemia which is in consonance with other studies conducted by other authors Khodke et al, Tilak et al 13,14 . The studies conducted by Kumar etal, Verma et al, Jha et al, Bhadracharya et al revealed Hypoplastic Anemia to be more common than Megaloblastic Anemia as a cause of pancytopenia 15,16,17 . A comparison of our results with those of other authors is shown in Table No.…”
Section: Methodsmentioning
confidence: 99%